Plagiognathus (Plagiognathus) raphani n. sp. (Hemiptera Heteroptera: Miridae). - Wagner, Eduard (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There is described a new species of the genus Plagiognathus from Lebanon. Nomenclatural Actsraphani Wagner, 1963 (Plagiognathus (Plagiognathus)), spec. nov.